Childfree: A Field Research in X District - Khoiruddin, Khoiruddin; Alsayd, Abdulnasir (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2025)
The issue of child labor in Indonesia is covered in this article. To be child-free is for a husband and wife to have mutually agreed not to procreate while they are married. Just hearing the term